Approach to neurorehabilitation in Contact Improvisation: Mark Young, a case study - Sebastián Gómez-Lozano; Clare Kelly-Lahon; Fulgencio Villescas Vivancos; Kiko Francisco León Guzmán (Revista del Centro de Investigación Flamenco Telethusa)
Contact improvisation is a postmodern dance style based on a continuum of proprioceptive communication between dancers. It has been established that proprioception is a factor utilized in certain neurorehabilitation techniques for different population groups, such as the Bobath Concept or Kabat Method. In deed there have been some studies into the application of Contact Improvisation strategies for rehabilitation purposes applied to prisoners and in the area of gender equality and to our knowledge, just one study in the field of neurorehabilitation with Parkinson’s patients. To this end, the main objective of our study is to analyze the common aspects of Contact Improvisation with regard to the process of applying neurorehabilitation strategies in order to establish a suitable theoretical-practical framework of work for future research. The methodology used was based on the analysis of a case study. This consisted of applying inquiry strategies through the medium of a semi-structured interview with Mark Young – a 53-year-old Contact Improvisation expert with 21 years of experience in that practice. The results showed a line of improvement in the subject’s symptoms of functional recovery. It would appear from this study that proprioception was key to the improvement in the neurological response of the individual practicing Contact Improvisation. In addition, there is a determinant and inherent social component to this process that seemed to facilitate and enhance the positive aspects of the practice of this form of dance.